Persistent hepatocyte secretory failure in lopinavir/ritonavir related to drug-induced liver injury: a case report - Sun, Yue; Wang, Ran; Wang, Cai'e; Shao, Xiaodong; Zheng, Xiaojie; Li, Hui; Chi, Yingkai; Deng, Baocheng; Li, Yiling; Jin, Shenghao; Qi, Xingshun (Frontiers in Medicine, 2025)
Lopinavir/ritonavir, an anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) drug, may be associated with the development of liver injury. In this paper, we reported an elderly female patient with drug-induced liver injury secondary to lopinavir/ritonavir, which was evaluated for their causality using the updated Roussel Uclaf Causality Assessment Method (RUCAM) of 2016. She had a RUCAM score of 8 which was equivalent to a probable causality grading. Her clinical course was complicated by persistent hepatocyte secretion failure (PHSF), followed by septic shock and SARS-CoV-2 re-infection during her hospitalization. Her response to any medical intervention, including ursodeoxycholic acid, glutathione, methylprednisolone sodium succinate, rifampicin, artificial liver support, and endoscopic nasobiliary drainage (ENBD) was very poor, and her family members refused liver transplantation. Finally, she died. In summary, this case suggests the possibility that lopinavir/ritonavir can cause DILI and even PHSF in our clinical practice.